The Impact of the 2008 Crisis on UK Prices: What We Can Learn from the CPI Microdata. (7th July 2020) - Dixon, Huw; Luintel, Kul; Tian, Kun
Abstract: This paper takes the locally collected price quotes used to construct the CPI index in the UK for the period 1996–2013 and explores the impact of the Great Recession (2008‐9) on the pricing behaviour of firms. We develop a time series framework which captures the link between macroeconomic variables and the behaviour of prices in terms of the frequency of price change, the dispersion of price levels and the size, dispersion and kurtosis of price‐growth. We find strong evidence for inflation having an effect, but not output. The change in the behaviour of prices during the Great Recession is largely explained by the changes in inflation and VAT. Nevertheless, the magnitude of the inflation effect is sufficiently small that it need not influence monetary policy.